2020
DOI: 10.26434/chemrxiv.12730964.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stable Cathode-Solid Electrolyte Composite for Long-Cycle-Life, High Voltage Solid-State Sodium-ion Batteries

Abstract: <p>Rechargeable solid-state sodium-ion batteries (SSSBs) hold great promise for safer and more energy-dense energy storage. However, the poor electrochemical stability between current sulfide-based solid electrolytes and high-voltage oxide cathodes has limited their long-term cycling performance and practicality. Here, we report the discovery of Na<sub>3-<i>x</i></sub>Y<sub>1-<i>x</i></sub>Zr<i><sub>x</sub></i>Cl<sub>6</sub&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…They mostly exhibit good chemical and electrochemical stability, [4] in sharp contrast to sulfide SEs with narrow electrochemical window, which also easily get decom-posed upon exposure towards humidity and oxygen. [5] However, high temperature sintering process (> 1200 °C) is always indispensable for the synthesis of oxides; and the ionic conductivity of oxide electrolytes (10 À 4 ~10 À 3 S cm À 1 ) is usually one order of magnitude lower than that of sulfides (10 À 3 10 À 2 S cm À 1 ), which will undisputedly restrict the capacity and the rate performance of ASSBs. [6] Hence, it is of great importance to explore oxide SEs with high ionic conductivity and preferably low sintering temperature from energy-saving point of view.…”
Section: Introductionmentioning
confidence: 99%
“…They mostly exhibit good chemical and electrochemical stability, [4] in sharp contrast to sulfide SEs with narrow electrochemical window, which also easily get decom-posed upon exposure towards humidity and oxygen. [5] However, high temperature sintering process (> 1200 °C) is always indispensable for the synthesis of oxides; and the ionic conductivity of oxide electrolytes (10 À 4 ~10 À 3 S cm À 1 ) is usually one order of magnitude lower than that of sulfides (10 À 3 10 À 2 S cm À 1 ), which will undisputedly restrict the capacity and the rate performance of ASSBs. [6] Hence, it is of great importance to explore oxide SEs with high ionic conductivity and preferably low sintering temperature from energy-saving point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The Xray diffraction (XRD) patterns of these samples revealed that the original trigonal P3m1 structure of Na 2 ZrCl 6 is retained across all variants (Figure 1a). 24,43 Specifically, up to x = 1.0, a gradual positive shift in the (301) peak at ∼30.5°with no emerging impurity phases suggests a lattice contraction in Na 2 ZrCl 6 , which is attributed to the smaller ionic radius of F − (133 pm) compared to that of Cl − (181 pm). 55 However, at x ≥ 1.5, the evolution of NaCl indicated a fluorination limit between x = 1.0 and 1.5.…”
mentioning
confidence: 98%
“…40,41 While fewer Na + halide SEs have been identified compared to their Li + counterparts, their development has followed similar patterns. 25 Na + halide SEs developed via composition tuning include Na 3−x Er 1−x Zr x Cl 6 (0.04 mS cm −1 ), 42 Na 3−x Y 1−x Zr x Cl 6 (0.066 mS cm −1 ), 43 Na 3−x Yb 1−x Zr x Cl 6 (0.066 mS cm −1 ), 44 Na 3−x Cr 1−x Zr x Cl 6 (0.1 mS cm −1 ), 45 and Na 3−x In 1−x Zr x Cl 6 (∼0.01 mS cm −1 ). 46 A significant enhancement in ionic conductivity has been observed in several compounds prepared using the mechanochemical method, such as Na 2 ZrCl 6 , NaAlCl 4 , and Na 3 InCl 6 .…”
mentioning
confidence: 99%
See 2 more Smart Citations